Novel biosorbents from almond shells: Characterization and adsorption properties modeling for Cu(II) ions from aqueous solutions. Issue 3 (June 2017) - Maaloul, Najeh; Oulego, Paula; Rendueles, Manuel; Ghorbal, Achraf; Díaz, Mario
Graphical abstract: Abstract: This study is focused on the adsorption of Cu(II) ions on chemically modified almond shell-based adsorbents, namely bleached almond shell (BAS), lyophilized-bleached almond shell (L-BAS), and TEMPO ((2, 2, 6, 6-Tetramethyl-piperidin-1-yl)oxyl) oxidized cellulose nanofibers (TOCN1 and TOCN2). Such materials were characterized by FTIR-ATR, N2 adsorption-desorption, SEM, TEM, and TGA/DTG. The adsorption isotherms and kinetics of Cu(II) onto the prepared biosorbents and the effect of temperature and pH on the removal efficiency were thoroughly analyzed. The maximum adsorption capacity of BAS, L-BAS, TOCN1 and TOCN2 at 30 °C and pH 6 was found to be 18.71, 28.27, 23.80, and 21.57 mg g −1, respectively. Therefore, these materials can be used as effective adsorbents for Cu(II)-containing wastewaters. The results of all the biosorbents, except for the BAS one, were fitted to the pseudo-first-order model with a good degree of concordance. It was also proved that the adsorption process onto L-BAS, TOCN1, and TOCN2 was exothermic and spontaneous.